Псалтирот на псалмописецот Давид - Дуев, Ратко (Филозофски факултет, Скопје, 2005)
Many Christian authors probably had no real idea which instrument they were calling a psalterium, nor were they really in a position to identify it with Hebrew nebel, the music instrument of King David. The most scholars understand it as a harp. However the archaeological findings, compared with the literary evidence point to certain facts that the nebel was a particular kind of lyre of local Near Eastern provenance, similar to kinnor. The translators of Septuagint and Vulgate understood the instrument as a psalterion – generic Greek word for a harp. This misunderstanding of nebel was transferred through the Old Church Slavonic Bible to Macedonian translation.
The Psalter of the Psalmist David